2015
DOI: 10.1002/casp.2232
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use Among Immigrant and Non‐immigrant Adolescents: Immigrant Paradox, Family and Peer Influences

Abstract: The present study compared immigrant and Italian native adolescents with regard to drug use. Additionally, we analysed the role of family and peer risk and protective factors for drug use. Participants included 2533 Italian native and immigrant adolescents (mean age = 17.19, SD = 1.6; 66.7% male). Results showed that immigrant adolescents reported lower levels of marijuana and pharmaceutical drug abuse than non-immigrant adolescents. These results confirm the so-called immigrant paradox phenomenon: the counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
(71 reference statements)
2
16
0
2
Order By: Relevance
“…The finding that being an immigrant was associated with lower odds of cannabis use also corroborates previous findings and provides further support for the immigrant paradox phenomenon. 31,32 These results support previous evidence suggesting that ethnoracial background should be an important consideration in investigations of cannabis use among foreign-born compared with nativeborn adolescents. 30 …”
Section: Discussionsupporting
confidence: 86%
“…The finding that being an immigrant was associated with lower odds of cannabis use also corroborates previous findings and provides further support for the immigrant paradox phenomenon. 31,32 These results support previous evidence suggesting that ethnoracial background should be an important consideration in investigations of cannabis use among foreign-born compared with nativeborn adolescents. 30 …”
Section: Discussionsupporting
confidence: 86%
“…While these factors suggest that migrant youths should display relatively low levels of wellbeing, several studies have found the opposite (Cristini et al, 2015;Harker, 2001;Harris, 1999;Vaage et al, 2009). Terms such as the healthy migrant effect, and the immigrant paradox phenomenon (e.g., Bowe, 2017;Fuligni, 1998;Marks, Ejesi, & Garcia Coll, 2014), have been coined to capture this effect.…”
Section: The Wellbeing Of Migrant Adolescentsmentioning
confidence: 99%
“…Although limited research has investigated the role of country of birth in moderating these effects, a case can be made for expecting migrant status to accentuate the positive effects of each of these psychosocial resources (c.f. Cristini et al, 2015) This case rests upon the likelihood that, relative to their native-born peers, migrant adolescents (a) face greater challenges and threats to their wellbeing, and (b) may have less social and economic capital with which to manage these challenges and threats. In such circumstances, migrant adolescents are likely to rely more heavily upon the resources they do possess, and hence such resources will be disproportionately impactful on their psychological adjustment (Gagne et al, 2014).…”
Section: School Membershipmentioning
confidence: 99%
“…Seven studies compared prevalence rates in migrant adolescents as one category and showed contrasting findings. Four studies reported lower prevalence rates of illicit drug use in migrants compared to natives [23,37,39,40], two reported higher prevalence rates in migrants compared to natives [23,42], and one reported similar prevalence rates for both migrants and natives [34].…”
Section: Resultsmentioning
confidence: 99%